Additional patients with 4q deletion: Severe growth delay and polycystic kidney disease associated with 4q21q22 loss. Issue 5 (28th October 2015) - Sakazume, Satoru; Kido, Yasuhiro; Murakami, Nobuyuki; Matsubara, Tomoyo; Numabe, Hironao
Abstract: Background: To the best of our knowledge, this is the third report concerning 4q21q22 deletions. In this report, we describe the cases of two girls with 4q deletion and polycystic kidney disease. G‐banding confirmed the deletion in one patient but not in the other. Methods: We describe the cases of two girls with 4q deletion and polycystic kidney disease. Chromosomal deletions were mapped to 4q21‐22. One patient had a simple 4q contiguous gene deletion, whereas the other patient had a complicated chromosomal rearrangement. In patient 1, a smaller part of the 4q deletion was translocated to the 3p region. Results: Fifty‐four genes and 72 genes were deleted in patients 1 and 2, respectively. In both patients, 52 genes were consistently deleted. Conclusion: The present two patients had a similar phenotype, including severe growth and developmental retardation, and a characteristic facial appearance. The loss of RPKG2 and RASGEF1B causes severe growth defect. PKD2 loss causes kidney cysts.